Action Reflected and Project Based Combined Methodology for the Appropriate Comprehension of Mechanisms in Industrial Design Education - H. Güçlü Yavuzcan; Damla Şahin (Journal of Education and Learning (EduLearn), 2018)
In industrial design education, mechanics-based courses are mainly based on traditional lecture and they are highly abstract for ID students to comprehend the mechanisms. The existing studies highlight the requirement of a new approach for mechanics-based courses in ID departments. The study presents, a combined teaching model of mechanism mainly based on applied teaching style and action learning to improve ID students' learning experience and competencies through promoting the transference of theoretical knowledge into practical experience and learning. The combined teaching model consisting of 3 phases was integrated to a design studio project that is mechanical game design. Project observations and post-questionnaire were employed to analyze objectively the appropriateness of the teaching model. The results indicated that, the combined teaching model improved ID students' learning outcomes and competencies in terms of transferring the gained theoretical and practical knowledge to the action learning.